Criteria for Data Validity in Qualitative Research - Masruroh Masruroh (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
Data validity in qualitative research pertains to validity and reliability adapted to the demands of scientific inquiry and the qualitative paradigm. Establishing data validity requires verification techniques based on specific criteria: credibility, transferability, dependability, and confirmability. Credibility refers to the alignment of data with reality, achieved through techniques such as prolonged engagement, persistent observation, triangulation, negative case analysis, and member checking. Transferability assesses the applicability of research findings to other contexts by providing comprehensive descriptions. Dependability ensures the reliability of research results through audits of the research process and outcomes. Confirmability emphasizes research transparency and objectivity by enabling others to evaluate and verify the findings. Qualitative research must employ these four criteria to ensure data validity and reliability that are scientifically sound and defensible.